Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/s0019-4832(12)60094-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music on systolic blood pressure, diastolic blood pressure, and heart rate: a meta-analysis

Abstract: There are a handful of studies that have been done investigating the effect of music on various vital signs, namely systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR). Many studies have also assessed effects of music on self-reported anxiety level, attributing some degree of music-induced anxiety relief to the beneficial impacts of music on vital signs. Several randomised studies have shown varying effects of music on these vital parameters and so a metaanalysis was done to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 20 publications
(20 reference statements)
7
63
2
3
Order By: Relevance
“…According to Agrawal et al the song "Weightless" by the Marconi Union band begins with a beat of 60 beats per minute and then falls gradually to 50 beats/minute and found that the heart rate slowly comes down to match the beat. 3 Similar results were also observed by Loomba et al 7 According to them, slow music has a beneficial effect in pre-operative setting and ICU, because it is found to reduce the heart rate, SBP and DBP.…”
Section: Effect Of Slow Musicsupporting
confidence: 70%
“…According to Agrawal et al the song "Weightless" by the Marconi Union band begins with a beat of 60 beats per minute and then falls gradually to 50 beats/minute and found that the heart rate slowly comes down to match the beat. 3 Similar results were also observed by Loomba et al 7 According to them, slow music has a beneficial effect in pre-operative setting and ICU, because it is found to reduce the heart rate, SBP and DBP.…”
Section: Effect Of Slow Musicsupporting
confidence: 70%
“…In the same meta-analysis, recorded music had a nominal effect on systolic blood pressure (z = 0.44) and diastolic blood pressure (z = 0.98) across studies (Zhang et al, 2012). In another meta-analysis, however, music therapy was shown to have a small to moderate effect on decreasing systolic and diastolic blood pressure (standard mean difference of -2.63) across studies (Loomba et al, 2012 Music and music therapy have had conflicting results regarding the effects of music on NICU patients (Standley, 2002), older adults and exercise (Clark et al, 2012), and patients with…”
Section: Music Therapymentioning
confidence: 90%
“…Music was shown to decrease heart rate in cancer patients (z = 2.32) (Zhang et al, 2012) and non-cancer patients (standard mean difference of -2.63) (Loomba et al, 2012) but not older adults during exercise routines (z = 0.80) (Clark et al, 2012). In a meta-analysis, Zhang et al (2012) found that recorded music had a large effect across studies on the decrease of respiratory rates in cancer patients (z = 5.16).…”
Section: Music Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…This proliferation of high quality scientific research in the field of clinical music therapy has generated significant level I evidence, suggesting that music therapy is capable of providing significant benefits as an adjuvant therapeutic tool in Treatment a wide variety of clinical settings . Furthermore, in the last decade, several meta-analyses and systematic reviews addressing the role of music therapy in specific clinical specialties have been performed [2][3][4][5][6][7][8][9][10] . This growing body of evidence provides robust scientific support for the hypothesis that music can positively influence several subjective and physiological variables related to anxiety and pain, significantly decrease pharmacological analgesia and sedative requirements, and make a meaningful improvement in mood and quality of life measures for a variety of patients .…”
Section: Introductionmentioning
confidence: 99%